2010
DOI: 10.1007/s11692-010-9091-6
|View full text |Cite
|
Sign up to set email alerts
|

Flower Development and the Evolution of Self-fertilization in Amsinckia: The Role of Heterochrony

Abstract: We studied the development of 26 flower traits under natural conditions in three clades of the genus Amsinckia (Boraginaceae). Each clade contained both a derived highly self-fertilizing taxon and an ancestral more highly outcrossing taxon. The more outcrossing taxa contained two flower morphs-pins and thrums-with opposite positioning of the sex organs (heterostyly). The highly selfing taxa had smaller flowers with sex organs in close proximity (homostyly). Growth trajectories were quantified over the entire o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…The "law" was translated to plants by Tucker (1997) as "the hierarchicalsignificance hypothesis," in which she postulated that characters of families will appear in early development, whereas characters of genera appear later and characters of species later still. The hypothesis has been supported by Tucker's own work on legumes and by some aspects of development in Amsinckia (Boraginaceae; Li and Johnston 2010).…”
Section: Discussionmentioning
confidence: 87%
“…The "law" was translated to plants by Tucker (1997) as "the hierarchicalsignificance hypothesis," in which she postulated that characters of families will appear in early development, whereas characters of genera appear later and characters of species later still. The hypothesis has been supported by Tucker's own work on legumes and by some aspects of development in Amsinckia (Boraginaceae; Li and Johnston 2010).…”
Section: Discussionmentioning
confidence: 87%
“…The species is a member of Boraginaceae, the family that has the largest number of independent origins of heterostyly, and this type of breeding system has evolved multiple times in Lithospermum L. (Cohen, 2011). Cohen et al (2012) demonstrated that there are differences in the development of the flowers within the genus, and data concerning SI and floral morphology and development based on studies by Philipp and Schou (1981), Casper (1985), Li and Johnston (2010), Ferrero et al (2012), and Cohen (2014) suggest that heterostyly evolved following distinct patterns in different tribes of the family. Heterostyly arose independently in L. mulitflorum , and the species is sister to Lithospermum macromeria .…”
Section: Introductionmentioning
confidence: 99%
“…). Despite these studies, however, it remains mostly unknown which developmental changes underlie the evolution of hermaphrodite sex allocation under selfing and/or outcrossing (Li and Johnston ; Roels and Kelly ; Noel et al. ).…”
mentioning
confidence: 99%